Factors Affectıng Heart Faılure Patıents’ Knowledge About Theır Diseases And Self-Care Behavıors: A Sample From Iraq - Al-Ghazali , Ali Hasan Nomas; Balkaya , Nevin Akdolun (Medical Science Journal for Advance Research, 2025)
Background: Self-care, which is one of the indispensable components of heart failure management, is accepted as a universal approach to reduce the utilization of health services (including hospital admissions) and improve heart failure outcomes. Aim: This study aimed to determine the factors affecting knowledge and self-care behaviors of individuals with heart failure regarding their disease. Method: The descriptive-cross-sectional study was conducted on 200 patients who applied for Al-Sadder Medical Center in Al-Nejef City, Iraq, to treat and control heart failure. The data were collected on 01.05.2021- 28.07.2021 based on self-reports with the Introductory Information Form, the Arabic Dutch Heart Failure Knowledge Scale (A-DHFKS), and the Arabic the Self-care of Heart Failure Index (A-SCHFI). Data were evaluated with descriptive statistics, t-test, one-way ANOVA, Mann Whitney U, Kruskal-Wallis H, correlation, and linear regression tests. Tukey and Dunnett were used for post hoc tests. Statistical significance was taken as p<0.05. Results: The patients’ heart failure knowledge and self-care are low (Arabic Dutch Heart Failure Knowledge Scale: 4.73±2.01, Arabic the Self-care of Heart Failure Index: 37.67±11.35, Self-Care Maintenance:36.87±10.13, Self-Care Management: 45.25±13.98, Confidence in Providing Self-Care: ‎‎30.88±20.41). ‎Heart failure knowledge scores were higher in those who discussed their problems with a doctor/nurse (p<0.05). Self-care scores increase in cases of high heart failure knowledge, high school and higher education, regular health check-ups for the disease, and knowing the name and effects of the drugs used, and decrease with smoking (p<0.05). Conclusion: The patients’ knowledge and self-care about heart failure are insufficient, and they are affected by various factors. In order to increase the knowledge of heart failure and patient self-care, it is recommended that health personnel, especially nurses, organize and maintain planned cardiac education programs that should include the affecting factors.